Implementation of Vocational College Lecturers Teaching Practice in Construction Technology Program - bin Halimoon, Hasrul; Roddin, Rohayu; Yusof, Yusmarwati; Nasir, Noor Izwan; Mukhtar, Marina Ibrahim (Online Journal for TVET Practitioners, 2023)
The research was conducted to identify practical teaching practices among lecturers of Construction Technology in Vocational College Malaysia. This research uses quantitative methods (questionnaires) and is supported by interview methods and observations for data collection and subsequently determines the answers to the identified research problems. There are three teaching practice components, namely pre-teaching practice, practice during teaching, and post-practice practice. The elements contained in the pre-teaching component of the lesson are the preparation of lesson plans, the provision of teaching aids and the preparation of lesson content. The current practice element of teaching is the teaching method and the element of post-practice practice is training and evaluation. The respondents involved were 46 Construction Technology lecturers at six Vocational College. The data obtained through pilot studies have been tested and demonstrated the reliability of Alpha Cronbach which is 0.819 high. An overview of the differences in pre-teaching practice, during teaching and post-lessons according to the experience and expertise category uses the T test with a significant level of 0.05. In overall, the findings show that all three components of pre-teaching practice, during teaching and post-teaching are at a high level. The findings also showed that there were no significant differences in pre-teaching practices, teaching and post-lectures based on the experience and expertise categories of lecturers.